The Impact of Macroeconomic Variables on the NEPSE Index: An ARDL Approach - Joshi, Mahesh (Indian Journal of Research in Capital Markets, 2024)
Purpose : The study aimed to investigate the impact of significant macroeconomic variables on the Nepal Stock Exchange (NEPSE) Index. Correlations between the NEPSE Index and macroeconomic variables including the weighted average lending rate, total deposits, inflation, broad money (M2), and gross foreign currency reserves—must be examined, both historically and prospectively. These links must be thoroughly understood by lawmakers, economists, financial investors, and economic policymakers. Methodology : For short-term and long-term correlations between the NEPSE Index and certain macroeconomic factors, the study used an autoregressive distributed lag (ARDL) model. Data were collected from the Nepal Rastra Bank website for the period from June 2017 to April 2024. The tests for heteroscedasticity, serial correlation, and normality were included in the model diagnostics, along with the Phillips–Perron test, which was used to determine if the data were stationary. Findings : The results demonstrated how the NEPSE Index, gross foreign exchange reserves, and general economic trends have a significant long-term impact on the stock market index. The short-run study indicated that changes in the NEPSE Index and broad money (M2) had a significant effect on the dependent variable. The bound test verified a long-run equilibrium connection between the variables. The Granger causality tests showed a bidirectional causal relationship between the NEPSE Index and broad money (M2). Practical Implications : The study emphasized the significance of broad money (M2) and gross foreign currency reserves in influencing the NEPSE Index. The bidirectional link between monetary circumstances and stock market performance demonstrated the interconnectedness of these variables. Policymakers should consider these links while developing stable economic policies that support stock market expansion. The NEPSE Index’s factors may be better understood if additional variables or advanced econometric techniques are researched. Originality : The study showed how macroeconomic variables affected the NEPSE Index using an ARDL methodology. For investors and policymakers in Nepal, the research provided important information by highlighting the importance of broad money (M2) and gross foreign currency reserved across both short and long-term horizons. Granger causality tests were applied to enhance the robustness of the findings and give a fuller understanding of the dynamic interactions between these variables.